The Cardioprotective PKA-Mediated Hsp20 Phosphorylation Modulates Protein Associations Regulating Cytoskeletal Dynamics - Vafiadaki, E.; Arvanitis, DA; Eliopoulos, A. G.; Kranias, EG; Sanoudou, D. (Int J Mol SciInt J Mol SciInt J Mol Sci, 2020)
The cytoskeleton has a primary role in cardiomyocyte function, including the response to mechanical stimuli and injury. The small heat shock protein 20 (Hsp20) conveys protective effects in cardiac muscle that are linked to serine-16 (Ser16) Hsp20 phosphorylation by stress-induced PKA, but the link between Hsp20 and the cytoskeleton remains poorly understood. Herein, we demonstrate a physical and functional interaction of Hsp20 with the cytoskeletal protein 14-3-3. We show that, upon phosphorylation at Ser16, Hsp20 translocates from the cytosol to the cytoskeleton where it binds to 14-3-3. This leads to dissociation of 14-3-3 from the F-actin depolymerization regulator cofilin-2 (CFL2) and enhanced F-actin depolymerization. Importantly, we demonstrate that the P20L Hsp20 mutation associated with dilated cardiomyopathy exhibits reduced physical interaction with 14-3-3 due to diminished Ser16 phosphorylation, with subsequent failure to translocate to the cytoskeleton and inability to disassemble the 14-3-3/CFL2 complex. The topological sequestration of Hsp20 P20L ultimately results in impaired regulation of F-actin dynamics, an effect implicated in loss of cytoskeletal integrity and amelioration of the cardioprotective functions of Hsp20. These findings underscore the significance of Hsp20 phosphorylation in the regulation of actin cytoskeleton dynamics, with important implications in cardiac muscle physiology and pathophysiology.
Keywords: 14-3-3 Proteins/metabolism; Actins/metabolism; Animals; Cofilin 2/metabolism; Cyclic AMP-Dependent Protein Kinases/*metabolism; Cytoskeleton/*metabolism; HEK293 Cells; HSP20 Heat-Shock Proteins/genetics/*metabolism; Humans; Mice; Mutation; Myocardium/*metabolism; Phosphorylation; Protein Binding; Protein Processing, Post-Translational